دور المراقب المالي في حوكمة تسيير المرفق العام - حمايتي, صباح; فريجات, إسماعيل (University of Eloued جامعة الوادي, 2021)
تطرقنا من خلال هذه الورقة البحثية إلى دور وجود المراقب المالي إلى جانب الإدارة، واعتبارها خطوة سديدة، فنتيجة لذلك تحقق أهم أهدافها المتمثلة في اكتشاف الانحرافات والتجاوزات الإدارية قبل حدوثها، والتي تعتبر من أنجع أنواع الرقابة التي يمارسها المراقب المالي على مختلف أوجه التسيير للمرفق العام وفقا لشروط وإجراءات محددة قانونا، سواء في تسيير شؤون الموظفين أو في مجال الصفقات العمومية والتي طبقناها على الجماعات المحلية، الأمر الذي يبرز مساهمة هذا الإجراء التنظيمي في ضمان تسيير وحوكمة نفقات المرفق العمومي لمختلف نشاطاته. Abstract Through this research paper, we touched upon the role of the financial controller’s presence alongside the administration and considering it a sound step, which as a result achieves its most important objectives, which is the discovery of deviations and administrative abuses before they occur, which is considered one of the most effective controls that the financial controller exercises over the various aspects of the management of the public utility according to the terms and conditions Legally defined procedures, whether in the management of personnel affairs or public deals, which they applied to local groups, which highlights the contribution of this regulatory action to ensuring the management and governance of the expenses of the public utility for its various activities.
The role of the financial controller in the governance of public utility
مقال
Keywords: المراقب المالي ; الحوكمة ; الموظفين ; المرفق العام ; النفقات العمومية; Financial Controller ; Governance; employees; General facility; Public expenditure.